Russian regulatory system for clinical trials is consistent with international approaches - Yu. N. Linkova (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Clinical trials are the most important stage in the development of effective and safe medicinal products. Yu.N. Linkova, Candidate of Medical Sciences, Vice President for Clinical Research and Development at BIOCAD, shares her perspective on clinical trial regulation in the Russian Federation.